BlaOXA-48 Genotypic Detection of Carbapenem Resistance in Isolates of Pseudomonas Aeruginosa - Shaista Bakhat; Yasmeen Taj; Faisal Hanif; Saman Nadeem (Journal of Bahria University Medical and Dental College)
Objective: To determine the prevalence of carbapenem resistance in strains of Pseudomonas aeruginosa at a molecular level by detecting OXA-48 gene which transcribe for resistance to the antibiotic carbapenem among indoor patients of a tertiary care hospital Karachi. Study Design and Setting: This observational cross-sectional study was conducted from September 2018 to May 2019 at PNS Shifa hospital of Karachi. Methodology: Total 140 strains of Pseudomonas aeruginosa were received and cultured from pus samples. These samples were collected from different wards like medicine, surgery, burn unit, ICU, ENT, plastic surgery, paedriatic and family ward. Carbapenem resistance was screened phenotypically by AST (Antibiotic susceptibility test), MHT (Modified Hodge test) and mCIM (Modified Carbapenem Inactivation Method) in all samples. Only in resistant cases OXA-48 gene was detected by real time PCR (polymerase chain reaction). Data was analyzed by following the proper loading sequence on product specification sheet. Data was statistically analyzed by SPSS version 23.0. Results were expressed as frequencies (percentages). Results: Out of 140, 17 (12%) were found to be resistant to carbapenem by AST, 20 (14%) by MHT, 25 (17.8%) by mCIM. Out of 25 resistant cases, 4 (16%) presence of OXA-48 gene by real time PCR were detected. Conclusion: OXA-48 gene showed 16% carbapenem resistance in this study. Pseudomonas aeruginosa is an opportunistic organism which causes multidrug resistance especially in hospitalized patients. Carbapenem is the last resort for serious infections.